AFTA DAN KUALITAS LINGKUNGAN HIDUP DI INDONESIA - Michael Gilbert (Center for Economic Studies Universitas Katolik Parahyangan, 2017)
The effect of economic integration on environmental quality in the member country is still debatable. Economic intergration is believed to increase economic activity in the country, and if Environmental Kuznets Curve (EKC) hypothesis is confirmed, increased national income will accelerate the environmental quality improvement. Indonesia is the member of several economic integrations, including AFTA. This study aims to investigate the effect of AFTA on environmental quality in Indonesia, through investigating Environmental Kuznets Curve (EKC). An Ordinary Least Square (OLS) regression analysis is employed, and CO2 emission as environmental quality indicator is used as dependent variable (it was planned that this study also used forest cover, and SO2 emission, as dependent variables; but data limitation problem on those variables has withdrawn the plan). Two independent variables, namely: number of population and economy opennes, other than Indonesia’s GDP per capita. The result suggests that AFTA does not affect the environmental quality in Indonesia.Keywords: Economic Integration, AFTA, environmental quality, Environmental Kuznets Curve